ANALISIS SISTEM ENERGI AEROBIK DAN ANEROBIK DALAM MENINGKATKAN PERFORMA ATLET (STUDI LITERATUR) - ZULFIKAR FIRMAN, MUH. FATHI; Zulkifli; Fadli; Muhabbah, Al Ikhsanul; Rambung S, Matelda; Kamaruddin, Ilham (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of in improving athletic the aerobic and anaerobic energy systems performance through a literature review. The method used is a literature review using a descriptive qualitative approach. Data were obtained from 20 national scientific articles published between 2016 and 2026, collected through databases such as Google Scholar, Garuda, and SINTA. The data analysis methods used include data reduction, data presentation and conclusion drawing. The results of the study show that aerobic energy system influences increased endurance and cardiovascular capacity in athletes, while the anaerobic energy system contributes to increased strength, speed, and muscle explosiveness. Training methods such as interval training, HIIT, and fartlek are effective in improving both aerobic and anaerobic energy systems. Furthermore, combining aerobic and anaerobic energy systems provides more optimal results for improving athletic performance than using only one system alone. The conclusion of this study shows that balanced development between aerobic and anaerobic energy systems plays a vital role in athletic performance. Therefore, it is necessary to develop a comprehensive training program tailored to the needs of each sport.